MOTIVASI, KEPUASAN ATAS KOMPENSASI, KOMITMEN ORGANISASI, DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN BAGIAN AKUNTANSI PADA PT PERUMNAS JAWA TIMUR - Ineke Dyan Oktaviana; Rovila El Maghviroh; Laila Saleh (The Indonesian Accounting Review, 2012)
Recently, almost some aspects of human lives have been affected by the fast growth due to the era of emerging globalization. In that case, human resources were considered instrumental in the success of a company, especially in providing the quality for the consumers. One way that companies can do is to manage human resources by improving employees’ work performance. The purpose of this study is to find out whether there is an influence of motivational variables, satisfaction of the compensation, organizational commitment, and work environment variables towards the job performance of employees in the accounting department at state-owned enterprise of Perumnas (National Housing). It used the sample with the employeesof state-owned enterprises at Perumnas using multiple linear regression analysis.From the analysis of variables, it was found the conclusion of motivation and satisfaction of compensation both have significant influence towards the achievement of the accounting department employees working on state-owned enterprises of Perumnas in East Java. Yet, the variables of organizational commitment and work environment have no significant influence on the work performance of employees at state-owned companies of Perumnas in East Java.